Unraveling NFT Purchase Intention: The Role of Visual Attractiveness, Perceived Risk, and Enjoyment - Ramjan, Sarawut; Sangkaew, Purimprach (Journal of Cultural Analysis and Social Change, 2026)
This research delves into the factors influencing the purchasing behavior of metaverse users in Thailand using PLS-SEM. While the results show that social influence, ease of use, and personal innovation have no effect on NFT purchase intention, NFT purchase intention is strongly influenced by price value, perceived risk, visual attractiveness, perceived enjoyment, and facilitating factors. The findings point to theoretical implications that suggest new factors related to new technology like NFT purchase intention, as well as practical implications for developers, marketers, and policymakers to employ appropriate strategies in creating such digital assets. Overall, this research seeks to promote safe and beneficial digital transformation for users and businesses worldwide.